IMPLEMENTATION OF PANCASILA VALUES BY MILLENNIAL GENERATION AS AN EFFORT TO CULTIVATE NATIONALISM SPIRIT IN GLOBALIZATION ERA - Muhammad Farid Yudistira Harimurti; Regina Rania Cahya Kusumaningrum; Eka Suci Rohmadani; Moses Glorino Rumambo Pandin (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2021)
Background: In this globalization era, there are many things that disrupt the original ways to behave as an Indonesian such as the influence of western culture that are not welcome by the ideology of Indonesian, Pancasila, which creates the urge of millennials to align this matter and make change with implementing the values of Pancasila in daily life to maintain the nationalism spirit. Method: This research used qualitative approach method using literature review and quantitative approach method by doing a survey with non-probability sampling and purposive sampling techniques with university students as the respondents. Aim: This research is conducted to know how well the millennials implements the value of Pancasila and also find the solution to increase the awareness of the millennials about the values of Pancasila and adopting it in their behavior. Result: The millennials have not implement values of Pancasila as a whole in their lives. Discussion: Pancasila is the foundation and the basis of Indonesia that guides the life of the nation. By implementing Pancasila values, it would grow the nationalism spirit in millenials. In this globalization era, technology is developing very rapidly, this affects the behavior of the millennials in implementing Pancasila values. Millennials have not implement the values of Pancasila as a whole nor completely nowadays, this has the potential to eliminate the spirit of nationalism in millenials. There are several solutions to overcome this situation by providing education about the values of Pancasila through several ways include utilizing the growth of technology. Suggestion: Millennials should have the ability to filter the influences in this globalization era and should implement values of Pancasila as a whole in daily lives. Limitations: This research has some limitations that it’s difficult to do an offline research and observation because of this pandemic Covid-19 situation.